Three Lines Of Defense: A Form Of Reinforcement Of Village Owned Enterprise - Intiyas Utami; Aprina Nugrahesthy Sulistya Hapsari; Yohanes Yakobus Werang Kean; Natasia Alinsari (Universitas Muhammadiyah Malang, 2022)
This study aims to explore the controls implemented in Village Owned Enterprises (BUMDes) financial management from the perspective of the three lines of defense at BUMDes